Synthesis and Diels-Alder Reactivity of Substituted [4]Dendralenes. - Saglam, M.; Alborzi, A.; Payne, Alan; Willis, A.; Paddon-Row, M.; Sherburn, M. (American Chemical Society, 2016)
The first synthesis of all five possible monomethylated [4]dendralenes has been achieved via two distinct synthetic strategies. The Diels-Alder chemistry of these new dendralenes (as multidienes) with an electron poor dienophile, N-methylmaleimide (NMM), has been studied. Thus, simply upon mixing the dendralene and an excess of dienophile at ambient temperature in a common solvent, sequences of cycloadditions result in the rapid generation of complex multicyclic products. Distinct product distributions are obtained with differently substituted dendralenes, demonstrating that dendralene substitution influences the pathway followed, when a matrix of mechanistic possibilities exists. Dendralene site selectivities are traced to electronic, steric and conformational effects, thereby allowing predictive tools for applications of substituted dendralenes in future synthetic endeavors.